PELAYANAN PEMBUATAN AKTA KELAHIRAN PADA KANTOR DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA PEMATANGSIANTAR - Yohana Anggriani Lumbantobing; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
A general public service or any form of service, either in the form of public goods and public services are in principle be the responsibility of and implemented by the relevant agencies, in an effort to meet the needs of society as well as in the implementation of the provisions of the legislation. But the services provided by government officials still raises a lot of complaints from the public that result in an adverse impact on government agencies. Types and methods of research used is descriptive research, which can be interpreted as a problem-solving process was investigated by depicting or describing the state of the subject and the object of research at the present time based on the facts that appear or how it is. While the methods used are qualitative research methods to describe the actual situation in detail and by looking at the actual problem and research objectives. The results showed that the presence of some inhibiting factors both from the government and from the public regarding birth certificates. From the government side it can be concluded that there are such constraints on government that takes care of the issuance of birth certificates. So the number of birth certificates in Pematangsiantar was still very low. So is the case of the people in the city itself Pematangsiantar there are several obstacles facing the community include, lack of public understanding about the importance of having a birth certificate, then a low level of education and uncomfortable service provided by the Office of Population and Civil City Pematangsiantar. Keywords: Service, Making Birth Certificate.